The psychological and social model for building a family in Qur'an and Sunnah in light of the modern era changes - Najmiah, Omar; Wafa' Abdullah, Abdel Qaher Al-Salahi; Yusof Ahmed, muhammad al-Abyadh (2020)
In light of cultural, political, and economic changes and all the conflicts, crises and transformations existed in our contemporary world, the family entity is directly affected and exposed to many problems both positive and negative ones. And from here, the problem of this research emerges, where it necessitated an urgent need for the Muslim family and the Muslim community in general to know the ideal model for a family in the Qur’an and the Sunnah of the Prophet including solutions and treatments devised by Islamic legislation for the entity of the Muslim family and its changes throughout the ages. The importance of this research comes from the need of the Muslim community for new visions that contribute to the stability of the family and the care of its interests, and appropriate social and psychological models for the upbringing of the generations. Moreover, due to the absence of a clear and flexible Qur'anic model in the family’s field from the educational, media, and social reform centers curricula, the misunderstanding that was followed by misbehavior within the family’s framework, and the impact of the variables that led to the neglecting of the rights and duties among family members, it was necessary to write about the topic of the family in the Qur’an and the Sunnah from more than one angle. I chose the descriptive approach to highlight the verses and hadiths that established the rules of a happy and stable life for the Muslim family and showing the impact of the changes in contemporary reality on them. The results showed the need for the Muslim community today to the social solutions and a great need to understanding the family model in Islam in addition to what scholars and specialists have offered regarding solutions and treatments for contemporary problems.